Eger Vaughan Murphree papers - Murphree, Eger Vaughan, 1898-1962.
Correspondence, memoranda, speeches, reports, newspaper clippings, biographical material, photographs, and other papers relating primarily to Murphree's activities as president of Esso Research and Engineering Company, the research and development branch of Standard Oil Company of New Jersey, and as an official of the fifth World Petroleum Congress. Includes correspondence concerning admission of Soviet scientists into the United States. Correspondents include William Sterling Byrd Lacy, John A. McCone, Richard M. Nixon, Glenn Theodore Seaborg, Lewis L. Strauss, and Edward Teller.
Scientist, engineer, and businessman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Lacy, William Sterling Byrd, -- 1910-1978 -- Correspondence; McCone, John A. -- 1902-1991 -- Correspondence; Nixon, Richard M. -- 1913-1994 -- Correspondence; Seaborg, Glenn Theodore, -- 1912- -- Correspondence; Strauss, Lewis L. -- Correspondence; Teller, Edward, -- 1908-2003 -- Correspondence; Esso Research and Engineering Company; Standard Oil Company of New Jersey; Petroleum industry and trade; Petroleum industry and trade -- Congresses; Science -- International cooperation; Scientists -- Soviet Union; Businessmen; Engineers; Scientists